INDIGENOUS PEOPLE, INDIGENOUS WORSHIP - Kanichikattil, Francis (Journal of Dharma, 2006)
Worship or religious cult plays an important role in the human destiny. The essence of religion is more intelligible in worship form than mere statement of its principles. Cult expresses a fundamental attitude of the human being because it manifests a relationship, namely a relationship between human being and the Divine. It affects the totality of one’s being and he or she makes use of signs and symbols in order to express this relationship. Therefore, signs and symbols have got an important place in human life. Objects, gestures, colours, paintings, sound, etc., are symbols that contain experience of the Reality and they bridge the gap between the visible and the invisible. A religious symbol always contains the experience of the Divine.